1981
DOI: 10.1084/jem.153.4.897
|View full text |Cite
|
Sign up to set email alerts
|

Polyspecific monoclonal lupus autoantibodies reactive with both polynucleotides and phospholipids.

Abstract: The diversity of autoantibodies produced in systemic lupus erythematosus (SLE) 1 (1) differentiates this disease from other autoimmune disorders in which the autoantibodies react with a narrow range of antigenic determinants. In autoimmune thyrotoxicosis (2), myasthenia gravis (3), and autoimmune hemolytic anemia (4), as examples, the diversity of autoantibody reactions is limited by comparison with the serological findings in SLE. A typical lupus serum can react with nucleic acids (native or denatured DNA; RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
1
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(128 citation statements)
references
References 15 publications
7
119
1
1
Order By: Relevance
“…S4). Assessment of reactivity with other self antigens, including cardiolipin and a panel of anti-nuclear antigens (23)(24)(25), revealed that matched antibodies trended to lower mean reactivity (in 6/6 antibody doses for cardiolipin and 35/36 antibody doses for anti-nuclear antigens) but did not reach statistical significance, likely because mismatched antibodies exhibited a broad range of reactivities ( Fig. S5 and Tables S4 and S5).…”
Section: Resultsmentioning
confidence: 99%
“…S4). Assessment of reactivity with other self antigens, including cardiolipin and a panel of anti-nuclear antigens (23)(24)(25), revealed that matched antibodies trended to lower mean reactivity (in 6/6 antibody doses for cardiolipin and 35/36 antibody doses for anti-nuclear antigens) but did not reach statistical significance, likely because mismatched antibodies exhibited a broad range of reactivities ( Fig. S5 and Tables S4 and S5).…”
Section: Resultsmentioning
confidence: 99%
“…Lafer et a1 (27) showed that monoclonal ssDNA antibodies from MRL-lpr mice cross-reacted with CL, PS, and PG. Koike et a1 (28) reported that anti-dsDNA activity in sera from patients with SLE was inhibited by CL.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity of anti-DNA antibodies with CL has been demonstrated using sera and monoclonal anti-DNA antibodies from SLE-prone mice, from normal individuals, and from SLE patients (2,(25)(26)(27)(28)(29). However, the P,-GPI dependence of these antibodies has not been examined.…”
mentioning
confidence: 99%
“…The prevalence and the clinical importance of these antibodies have also been discussed in relation to the occurrence of human and mouse monoclonal antibodies against denatured DNA, and their cross-reactivity with cardiolipin and other phospholipids (4)(5)(6).…”
Section: Anticardiolipin Antibodies In Patients With Systemic Lupus Ementioning
confidence: 99%